A ruthenium(II) complex-based lysosome-targetable multisignal chemosensor for in vivo detection of hypochlorous acid. (November 2015) - Cao, Liyan; Zhang, Run; Zhang, Wenzhu; Du, Zhongbo; Liu, Chunjun; Ye, Zhiqiang; Song, Bo; Yuan, Jingli
Abstract: Although considerable efforts have been made for the development of ruthenium(II) complex-based chemosensors and bioimaging reagents, the multisignal chemosensor using ruthenium(II) complexes as the reporter is scarce. In addition, the mechanisms of cellular uptake of ruthenium(II)-based chemosensors and their intracellular distribution are ill-defined. Herein, a new ruthenium(II) complex-based multisignal chemosensor, Ru-Fc, is reported for the highly sensitive and selective detection of lysosomal hypochlorous acid (HOCl).Ru-Fc is weakly luminescent because the MLCT (metal-to-ligand charge transfer) state is corrupted by the efficient PET (photoinduced electron transfer) process fromFc (ferrocene) moiety to Ru(II) center. The cleavage ofFc moiety by a HOCl-induced specific reaction leads to elimination of PET, which re-establishes the MLCT state of the Ru(II) complex, accompanied by remarkable photoluminescence (PL) and electrochemiluminescence (ECL) enhancements. The result of MTT assay showed that the proposed chemosensor, Ru-Fc, was low cytotoxicity. The applicability ofRu-Fc for the quantitative detection of HOCl in live cells was demonstrated by the confocal microscopy imaging and flow cytometry analysis. Dye colocalization studies confirmed very precise distribution of the Ru(II) complex in lysosomes, and inhibition studies revealed that the caveolae-mediated endocytosis played an important role during the cellular internalization ofRu-Fc . By usingRu-Fc as a chemosensor, the imaging of the endogenous HOCl generated in live macrophage cells during the stimulation was achieved. Furthermore, the practical applicability ofRu-Fc was demonstrated by the visualizing of HOCl in laboratory model animals, Daphnia magna and zebrafish.